CFD approach to determine the effect of nappe breakers on sub-atmospheric pressure variations downstream of Trapezoidal labyrinth weirs - Aydin, M. Cihan; Bilhan, Omer; Ulu, Ali Emre; Emiroglu, M. Emin (Taylor & Francis Ltd, 2026)
Trapezoidal labyrinth weirs, due to their increased crest lengths, can discharge more water for the same weir opening length and hydraulic head. However, due to their increased length and structural degrees of freedom, they can cause undesirable vibrations and oscillations under new flow conditions. In order to prevent these oscillations, it is necessary to somehow eliminate the negative pressures created under the unventilated water nappe on the downstream surface of the weir and the temporal and spatial variations of these pressures. These undesirable effects can be partially or completely prevented by the nappe breaker devices to be used on the labyrinth weirs. Within the scope of this study, the hydraulic performance of a trapezoidal labyrinth weir with and without nappe breakers was analyzed using a three-dimensional CFD-based numerical model under free-surface and turbulent flow conditions. The analysis results indicated that sub-atmospheric pressures in regions near the crest, where under-nappe pressures play a critical role, were reduced by 54%. Additionally, the hydrostatic pressures at the crest experienced an average reduction of 12%. Furthermore, the standard deviation of pressure fluctuations along the crest length, which could contribute to weir vibrations, was decreased by 27% due to the implementation of nappe breakers.
Keywords: Trapezoidal labyrinth weirs; nappe breaker; pressure fluctuation; nappe vibrations; CFD